Coupled magnetic Mie resonances induced extraordinary optical transmission and its non-linear tunability - Cai, Weiqi; Xuan, Lixin; Fan, Yuancheng; Yang, Ruisheng; Zhang, Wenwu; Zhang, Qing; Chen, Songnan; Ye, Zhehao; Zhang, Yujing; Fu, Quanhong; Zhang, Fuli (Frontiers in Materials, 2023)
Dielectric metamaterials with low ohmic losses and resonating in the local magnetic mode are preferable for enhancing material nonlinearity. Here, we propose and experimentally demonstrate broadband extraordinary electromagnetic transmission (EET) behavior, which is induced by the coupling of magnetic modes of two ceramic cuboids. It is shown that EET behavior through a perforated metal sheet with a subwavelength aperture can be achieved by exciting the first-order magnetic mode Mie resonant coupling of these cuboids. Our findings indicate that the transmission bandwidth and amplitude are dependent on the strength of coupling between the two ceramic cuboids. Additionally, we utilized nonlinear effects within the dielectric cuboids to achieve tunable EET behavior. Our results are promising for developing nonlinearly tunable microwave devices such as filters and modulators of their strong light-matter interactions.